Safety and clinical activity of JNJ-78306358, a human leukocyte antigen-G (HLA-G) x CD3 bispecific antibody, for the treatment of advanced stage solid tumors - Geva, Ravit; Vieito, Maria; Ramon, Jorge; Perets, Ruth; Pedregal, Manuel; Corral, Elena; Doger, Bernard; Calvo, Emiliano; Bardina, Jorge; Garralda, Elena; Brown, Regina J.; Greger, James G.; et al. (Cancer Immunology, Immunotherapy : CII, 2024)
Background JNJ-78306358 is a bispecific antibody that redirects T cells to kill human leukocyte antigen-G (HLA-G)-expressing tumor cells. This dose escalation study evaluated the safety, pharmacokinetics, pharmacodynamics, and preliminary antitumor activity of JNJ-78306358 in patients with advanced solid tumors. Methods Adult patients with metastatic/unresectable solid tumors with high prevalence of HLA-G expression were enrolled. Dose escalation was initiated with once-weekly subcutaneous administration with step-up dosing to mitigate cytokine release syndrome (CRS). Results Overall, 39 heavily pretreated patients (colorectal cancer: n = 23, ovarian cancer: n = 10, and renal cell carcinoma: n = 6) were dosed in 7 cohorts. Most patients (94.9%) experienced ≥ 1 treatment-emergent adverse events (TEAEs); 87.2% had ≥ 1 related TEAEs. About half of the patients (48.7%) experienced CRS, which were grade 1/2. Nine patients (23.1%) received tocilizumab for CRS. No grade 3 CRS was observed. Dose-limiting toxicities (DLTs) of increased transaminases, pneumonitis and recurrent CRS requiring a dose reduction were reported in 4 patients, coinciding with CRS. No treatment-related deaths reported. No objective responses were noted, but 2 patients had stable disease > 40 weeks. JNJ-78306358 stimulated peripheral T cell activation and cytokine release. Anti-drug antibodies were observed in 45% of evaluable patients with impact on exposure. Approximately half of archival tumor samples (48%) had expression of HLA-G by immunohistochemistry. Conclusion JNJ-78306358 showed pharmacodynamic effects with induction of cytokines and T cell activation. JNJ-78306358 was associated with CRS-related toxicities including increased transaminases and pneumonitis which limited its dose escalation to potentially efficacious levels. Trial registration number ClinicalTrials.gov (No. NCT04991740).